The clinical significance of neutrophil gelatinase‐associated lipocalin in ischemic stroke patients with acute kidney injury. Issue 6 (7th May 2019) - Xiao, Wei; Chen, Wei; Hu, Hanning; Huang, Xiaomei; Luo, Yi
Abstract: Background: Acute kidney injury (AKI) has become a common complication of acute ischemic stroke (AIS) and may have a significant impact on the clinical outcomes. Neutrophil gelatinase‐associated lipocalin (NGAL), an acute phase protein, has been identified as a novel biomarker for acute kidney impairment. Here, we studied the early expression of NGAL in AIS patients with AKI and its clinic value in predicting and diagnosis of AKI after stroke. Methods: A total of 205 subjects diagnosed as first‐ever AIS were recruited in this study, including 40 AIS with AKI and 165 AIS without AKI defined using the KDIGO guidelines. The serum and urine levels of NGAL were measured with ELISA. To evaluate the clinic value of NGAL, we also detected creatinine, urea nitrogen and cystatin C and microalbumin (mALB) in serum or urine using chemiluminescence or immunoturbidimetry method, and then the receiver operating characteristic (ROC) curve and correlation was analyzed. The severity of AIS patients was evaluated based on the National Institutes of Health Stroke Scale (NIHSS) score. Results: The serum and urine NGAL levels were significantly increased in AIS patients with AKI, and line regression analysis indicated that there was a positive correlation between the serum NGAL and creatinine level in AIS patients accompanied AKI. Additionally, the concentration of serum NGAL in AIS patients with AKI increased with the severity of stroke. Conclusion: The increased serum NGAL may be used as a valuable complementary marker for the diagnoses and prediction of AKI in the early stage of AIS patients.